Penentuan Rute Pembukaan Gerai Baru dengan Vehicle Routing Problem with Time Windows Pendekatan Nearest Neighbor - Hajar, Granita; Rachmaniar, Desita Nur; Fauzi, Muhammad Dzulfikar (Engineering Faculty at Universitas Singaperbangsa Karawang, 2024)
The food and beverage industry are gaining significant attention among the public, as evidenced by the increasing number of food and drink outlets emerging. In some cities, there are even dozens of outlets due to the high level of enthusiasm among people. One particularly popular type of drink outlet currently is boba or bubble tea. Previous research has been conducted to identify potential locations for new outlets. Following the recommendations for new outlets, the research continued by determining the delivery routes for raw materials. The objective of this research is to establish new distribution routes for existing beverage outlets across several locations to minimize travel distance and transportation costs. This study utilizes the Vehicle Routing Problem with Time Windows (VRPTW), which is the most used VRP model in the industrial sector. The results of this research yielded two routes, with distances of 96.4 km and 35.7 km respectively, and travel times of 289.2 minutes and 163.5 minutes.